Rare bird documentation form for Glaucous Gull at Lock and Dam 15 at Davenport, 1981 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1981)
Rare bird documentation form for a Glaucous Gull at Lock and Dam 15 at Davenport in Scott County, IA on January 2, 1981. Epson - sheet feed